Can Latin America Tap the Globalization Upside? - de la Torre, Augusto; Didier, Tatiana; Pinat, Magali (World Bank, Washington, DC, 2014)
This paper discusses the theoretical arguments in favor of and against economic globalization and, with a view to ascertaining whether Latin America may be able to capture the globalization upside, examines the trends and salient features of Latin America's globalization as compared with that of Southeast Asia. The paper focuses on trade and financial integration as well as the aggregate demand structures (domestic demand-driven versus external demand-driven) that underpin the globalization process. It finds that Latin America is mitigating some bad side effects of financial globalization by moving toward a safer form of international financial integration and improving its macro-financial policy frameworks. Nonetheless, Latin America's progress in raising the quality of its international trade integration has been scant. The region's commodity-heavy trade structures and relatively poor quality of trade connectivity can hinder growth potential to the extent that they are less conducive to technology and learning spillovers. Moreover, Latin America's domestic demand-driven growth pattern (a reflection of relatively low domestic savings) may become an additional drag to growth by accentuating the risk of a low savings-low external competitiveness trap.